Heavy Metal Contamination (Cu, Pb, Zn, Fe, and Mn) in Urban Dust and its Possible Ecological and Human Health Risk in Mexican Cities - Aguilera, Anahi; Cortés, José Luis; Delgado, Carmen; Aguilar, Yameli; Aguilar, Daniel; Cejudo, Ruben; Quintana, Patricia; Goguitchaichvili, Avto; Bautista, Francisco (Frontiers in Environmental Science, 2022)
Cities occupy a relatively small percentage of the earth's surface. However, they influence the entire biosphere, affect biodiversity and environmental conditions, which end up affecting human health and well-being. Therefore, it is necessary to evaluate the level of contamination by heavy metals in urban environments, as well as the possible ecological and human health risks. In this study, the urban dust of six Mexican cities was analyzed and it was found that all studied cities were contaminated, except for Mérida, when soil world background value was used as reference. In contrast, Mérida and Morelia were the most contaminated when a local background was used (decile 1). The concentrations in the cities for the metals Cu, Pb and Zn, decreased in the order CDMX > San Luis Potosí > Toluca > Morelia-Ensenada > Mérida. In the particular case of Cu and Pb, SLP accompanied CDMX as the most polluted city. For Mn and Fe concentrations, the order was CDMX > Toluca > Ensenada > SLP > Morelia-Mérida. No potential ecological risk was found due to contamination by Cu, Pb, and Zn, in the urban dust of the studied cities. However, the higher metal contribution to the potential ecological risk in all the cities was from Pb; and it represented a moderate ecological risk of more than 25% on CDMX, SLP, and Toluca sites. Pb can also be a potential risk for children's health. In addition, chronic exposure to Fe and Mn could trigger many ailments. In the future, it is important to identify the main sources of Pb in cities and seek mitigation strategies to reduce the possible adverse effects that this metal may be causing.